Patient-specific non-invasive estimation of pressure gradient across aortic coarctation using magnetic resonance imaging. Issue 6 (June 2019) - Shi, Yubing; Valverde, Israel; Lawford, Patricia V.; Beerbaum, Philipp; Hose, D. Rodney
Highlights: Inertial effect influences the pressure gradient in aortic coarctation. Using friction plus inertia can model the blood flow in aortic coarctation. Magnetic resonance imaging-based modeling produces agreeable results to the catheter-measured data. Abstract: Background: Non-invasive estimation of the pressure gradient in aortic coarctation has much clinical importance in assisting the diagnosis and treatment of the disease. Previous researchers applied computational fluid dynamics for the prediction of the pressure gradient in aortic coarctation. The accuracy of the prediction was satisfactory but the procedure was time-consuming and resource-demanding. Method: In this research a magnetic resonance imaging (MRI)-based non-invasive modeling procedure is implemented to predict the pressure gradient in 14 patient cases of aortic coarctation. Multi-cycle patient flow and pressure data are processed to produce the flow and pressure conditions in the patient cases. Bernoulli equation-based friction loss model combined with the inertial effect of the blood flow in the vessel segments are applied to model the pressure gradient in the aortic coarctation. The model-predicted pressure gradient data are then compared with the catheter in vivo measurement data for validation. Results: The MRI-based model prediction technique produces results that are consistent with those from the catheter measurement, based on the criteria of both the cycle-averaged instantaneous pressure gradient and the peak-to-peak pressure gradient. Conclusion: This study suggests that the MRI-based non-invasive modeling procedure has much potential to be applied in clinical practice for the prediction of the pressure gradient in aortic coarctation patients.